Ernest Armstrong McCulloch. 21 April 1926—20 January 2011. (30th April 2018) - Mak, Tak Wah
Abstract : Ernest Armstrong McCulloch was half of the brilliant partnership that discovered haematopoietic stem cells (HSCs) and changed how we think about human tissue generation and regeneration. Based at the Ontario Cancer Institute (now the Princess Margaret Cancer Centre) in Toronto, the haematologist 'Bun' McCulloch, together with James E. Till, a physicist with a steel-trap mind, exercised their penchant for adventurous 'big picture' thinking in devising experiments to identify stem cells. This exceptional team was the first to demonstrate that HSCs have the dual capacity to self-renew and to differentiate into a vast array of mature haematopoietic cells. Their trainees, as well as investigators elsewhere, built on McCulloch and Till's findings not only to isolate and characterize HSCs and progenitors derived from them, but also to devise therapies for certain blood disorders. Later in his career, Ernest focused on characterizing the malignant cells of human leukaemias and determining the effects of various drugs on leukaemic cell growth. The implications of Till and McCulloch's work continue to be profound and underpin many significant breakthroughs in our knowledge of normal cellular physiology, pathophysiology, tumorigenesis and tissue transplantation. Indeed, regenerative medicine owes its very existence to the stem cell discoveries of McCulloch, Till and others. At times eccentric and demanding, but always well spoken, incisive and erudite, Ernest personified the outstanding research scientist cloaked in Canadian modesty. His legacy lives on in the bright therapeutic future emerging from the rigorous stem cell research being conducted in Canada and around the world.